Radical trideuteromethylation with deuterated dimethyl sulfoxide in the synthesis of heterocycles and labelled building blocks. Issue 84 (4th October 2016) - Caporaso, Roberta; Manna, Srimanta; Zinken, Sarah; Kochnev, Alexander R.; Lukyanenko, Evgeny R.; Kurkin, Alexander V.; Antonchick, Andrey P.
Abstract : A selective introduction of trideuteromethyl groups for the synthesis of labelled compounds under radical reaction conditions is demonstrated. Abstract : The potential of deuterated pharmaceuticals is being widely demonstrated. Here we describe the first trideuteromethylation under radical reaction conditions using deuterated dimethyl sulfoxide as a reagent for the synthesis of labelled heterocycles and trideuteromethylated compounds. A broad scope of the developed method for the synthesis of various scaffolds was demonstrated.